2022
DOI: 10.23851/mjs.v33i3.1129
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Type 1 and Type 3 Fimbrial Genes with the Type of Specimen and the Antibiotic Resistance Profile of Clinically Isolated Klebsiella pneumoniae in Baghdad

Abstract: Klebsiella pneumoniae is a member of coliform bacteria that causes wide ranges of infections including circulatory, respiratory system, urinary tract infections (UTIs), and wounds infections. This study aimed to find the correlation between type 1 and 3 fimbrial genes expression with multidrug resistance (MDR) K. pneumoniae isolates towards antibiotics. Sixty clinical isolates of K. pneumoniae were collected from three main types of samples including blood, wound and burn swabs, and urine samples. The diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
3
1
0
Order By: Relevance
“…However, the prevalence of these resistance genes The current study demonstrated a high prevalence of resistance genes among patients infected with K. pneumoniae, indicating that treatment of these infections can be challenging and pose a significant risk to this population. These findings are consistent with those of Muhsin et al, who reported a high prevalence of efflux pump resistance genes among clinical isolates of K. pneumoniae in Baghdad, Iraq (24). Similar results were also observed in other studies conducted in different parts of the world (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…However, the prevalence of these resistance genes The current study demonstrated a high prevalence of resistance genes among patients infected with K. pneumoniae, indicating that treatment of these infections can be challenging and pose a significant risk to this population. These findings are consistent with those of Muhsin et al, who reported a high prevalence of efflux pump resistance genes among clinical isolates of K. pneumoniae in Baghdad, Iraq (24). Similar results were also observed in other studies conducted in different parts of the world (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Results showed that OmpK35 and OmpK36 were 39 (92.8%) and 32 (76.1%) respectively (Figure,4 and 5). In accordance with the findings of a previous investigation conducted in Baghdad by Muhsin et al, [29] they found the results was 51 (85%) of the total 60 isolates had positive results for OmpK35. Current results were high from finding was observed in Saudi Arabia by Ejaz [30] who discovered the Ompk36 result to be 72.5%.…”
Section: Detection Of Folate Pathway Inhibitors Genes Among Gentamici...supporting
confidence: 90%
“…These results are close to the findings of [19] and [20] regarding river water samples. It was recorded that the same water quality parameters as in the current study as the high levels of such heavy metals might affect the food chain, health, and fish in such ecosystems [21]. There was a significant difference in levels of certain metals compared to the others in the study [22].…”
Section: Resultssupporting
confidence: 59%